2005
DOI: 10.1017/s0022215105003567
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing dysfunction in patients with unilateral vocal fold paralysis: aetiology and outcomes

Abstract: Although unilateral vocal fold palsy (UVFP) is a common problem, data relating to swallowing dysfunction are sparse. We reviewed the clinical findings (method of presentation, underlying diagnosis and position of the vocal folds) of 30 patients and conducted a follow-up telephone survey. Outcome measures used were direct visualization of fold function, position and compensation. In addition, standardized speech and language assessments for swallowing dysfunction and dysphonia were noted and compared to present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 2 publications
1
60
0
Order By: Relevance
“…Most studies of patients with VCP have concluded that the main cause of dysphagia is the reduced mechanical protection of the glottis [46]. However, Tabaee et al [6] reported that pharyngeal sensory impairment is involved, and Battacharyya et al [8] suggested that diminished cough strength is also an important cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of patients with VCP have concluded that the main cause of dysphagia is the reduced mechanical protection of the glottis [46]. However, Tabaee et al [6] reported that pharyngeal sensory impairment is involved, and Battacharyya et al [8] suggested that diminished cough strength is also an important cause.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that nearly 56% of patients with VCP have swallowing dysfunction [4, 5]. Tabaee et al [6] suggested that dysphagia in patients with VCP has multifactorial causes, including limited airway protection and decreased laryngopharyngeal sensation based on the findings of flexible endoscopy.…”
mentioning
confidence: 99%
“…Therefore, it is difficult to identify, with certainty, swallowing hemispheric dominance for head and neck sensation and movement given the tasks from this study. Yet, unilateral paralysis (Ollivere et al, 2006) or paresis (Vigderman et al, 1998) of head or neck musculature can result in serious swallowing disability, as can unilateral cortical damage secondary to stroke (Daniels and Foundas, 1997; Robbins et al, 1993). The right-sided activity in the older group of the current study might indicate a normal shift toward right-hemispheric activity for swallowing with healthy aging.…”
Section: Discussionmentioning
confidence: 99%
“…The immobility may be caused by neck and thoracic surgery, which can impair the innervation of the pharynx, upper esophageal sphincter (UES), and proximal esophagus, but may also be due to malignancy, trauma, intracranial causes, or may be idiopathic [4,5].…”
Section: Introductionmentioning
confidence: 99%